2021
DOI: 10.1002/cmdc.202000915
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin‐Thiourea Hybrids Show Potent Carbonic Anhydrase IX and XIII Inhibitory Action

Abstract: A series of coumarin-thiourea hybrids (4 a-o) has been synthesized, and the compounds have been evaluated against the tumour associated transmembrane isoform, human (h) carbonic anhydrase (CA) hCA IX and the less-explored cytosolic isoform, hCA XIII. All compounds exhibited potent inhibition of both isoforms, with K I values of < 100 nM against hCA IX. Compound 4 b was the best inhibitor (K I = 78.5 nM). All the compounds inhibited hCA XIII in the low-nanomolar to sub-micromolar range, with compound 4 b again … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…These include sulfonamido carboranes 134 , 135 , benzenesulfonamides incorporating 1,3,4-oxadiazole hybrids 136 , benzimidazole derivatives 137 , 7-Acylamino-3H-1,2-benzoxathiepine 2,2-dioxides 138 , aryl derivatives of 3H-1,2-benzoxathiepine 2,2-dioxide 139 , S-substituted 2-mercaptoquinazolin-4(3H)-ones and 4-ethylbenzensulfonamides 140 , aryl selenols 141 , sulfocoumarins and coumarin derivatives 142–145 , coumarin-thiourea hybrids 146 , phenols, polyamines, carboxylates 147 , epacadostat 148 , pyridinium derivatives of 3-aminobenzenesulfonamide and sulfonamides containing various nitrogenous bases 11 , 149 , 150 and short peptide-constructed nanofibers 151 .…”
Section: Targeting Caix With Small Molecule Inhibitorsmentioning
confidence: 99%
“…These include sulfonamido carboranes 134 , 135 , benzenesulfonamides incorporating 1,3,4-oxadiazole hybrids 136 , benzimidazole derivatives 137 , 7-Acylamino-3H-1,2-benzoxathiepine 2,2-dioxides 138 , aryl derivatives of 3H-1,2-benzoxathiepine 2,2-dioxide 139 , S-substituted 2-mercaptoquinazolin-4(3H)-ones and 4-ethylbenzensulfonamides 140 , aryl selenols 141 , sulfocoumarins and coumarin derivatives 142–145 , coumarin-thiourea hybrids 146 , phenols, polyamines, carboxylates 147 , epacadostat 148 , pyridinium derivatives of 3-aminobenzenesulfonamide and sulfonamides containing various nitrogenous bases 11 , 149 , 150 and short peptide-constructed nanofibers 151 .…”
Section: Targeting Caix With Small Molecule Inhibitorsmentioning
confidence: 99%
“…[18] After that, the nitro group at position-5 of N-alkylated indole-3-sulfonamide was reduced in the presence of iron powder and acetic acid to obtain N-alkylated 5-aminoindole-3sulfonamide 5. [19] Finally, the target compounds 6a-ag were obtained in good quantity by reacting 5 with different isocyanates. [20] In this study, 33 compounds were synthesized, and their structures were confirmed by 1 H NMR (nuclear magnetic resonance), 13 C NMR, and high-resolution mass spectrometry (HRMS).…”
Section: Chemistrymentioning
confidence: 99%
“…The α‐CAs are found in vertebrates, protozoa, algae, and cytoplasm of green plants and in many Gram negative bacteria; the β‐CAs predominantly present in both Gram negative and positive bacteria algae and chloroplasts of mono‐ as well as di‐cotyledons, and also in many fungi and Archaea . The γ‐CAs are mainly seen in archaea, cyanobacteria and most types of bacteria; whereas the δ‐, ζ ‐ and θ‐CAs seem to be present only in marine diatoms, whereas the η ‐CAs in protozoa and the ι‐CAs are found in marine diatoms and bacteria [2–5] . Among all families only the α‐CAs class which is present in human and a total of 16 isozymes have been determined as members of the α‐CA family in mammals represented by human carbonic anhydrase (hCA) varies from hCA I to hCA XV.…”
Section: Introductionmentioning
confidence: 99%